ANALYSIS OF THE IMPACT OF SOCIAL MEDIA MARKETING ACTIVITIES IN BRAND LOYALTY WITH BRAND AWARENESS AS INTERMEDIATE VARIABLES (STUDY ON TRAVELOKA BRAND) - Romindo Pasaribu; Andryana Silalahi (LPPM Universitas HKBP Nommensen, 2020)
Social media marketing is a process of strategy and methods for building the influence, reputation and brand of a company in the community of potential customers, readers, or supporters. Company. The objectives of this study are: (1) To examine the effect of social media marketing activities on brand loyalty on the Traveloka brand? (2) To test the effect of social media marketing activities on brand awareness of brands on the Traveloka brand, and (3) To examine the effect of social media marketing activities on brand loyalty and brand awareness as intermediary variables on the Traveloka brand ?. This study uses a survey method with primary data collection techniques. The research population is potential customers and the public who have seen social media marketing activities carried out by Traveloka Applications. The results showed that there was a significant influence between social media marketing activity variables on the Traveloka brand loyalty in Medan. There is a significant influence of social media marketing activity variables on the Traveloka brand awareness in Medan. There is a significant influence of social media marketing activity variables on the Traveloka brand awareness in Medan.